Catalyzing urban redevelopment on Washington Avenue - St. Louis, Missouri - Zundel, Bryan Christopher (Kansas State University, 2012)
In many urban redevelopment discussions, people often refer to a catalyst as the impetus for redevelopment. Unfortunately, no standard definition of an urban redevelopment catalyst exists, so liberal use of the term catalyst persists. As distinguished in Dr. Timothy Chapin’s dissertation, Urban Revitalization Tools: Assessing the Impacts of Sports Stadia at the Microarea Level, the impacts of sports stadia (widely considered catalysts) are often overstated. In order to have valuable arguments over the impacts of presupposed catalytic activities, we need to understand the defining characteristics of an urban redevelopment catalyst and utilize a consistent process for examining them. This study identifies these characteristics and develops a methodology from which others may study catalysts. Included in the study are both narrative and tangible evidence from which researchers may decipher catalytic characteristics and events. In order to explore this analytic method, a case study was necessary. The revitalization of Washington Avenue (in downtown St. Louis, Missouri) provided an excellent opportunity to implement and test the process. Washington Avenue went from decrepit in the early 1980s to receiving the honor of being a Great Street by the American Planning Association in 2011. By delving into the developmental history of Washington Avenue, the process verified urban redevelopment catalytic characteristics, the methodology and the presence of small-scale urban redevelopment catalysts. From these findings, (coupled with a preexisting, dominant discussion focused large-scale catalysts) we see the value of small, organic development. The study prompts further exploration of urban redevelopment catalysts, especially in regards to smaller catalysts. It also suggests a new line of thinking for urban redevelopment dynamics, thus guiding future research to focus on understanding the processes of urban redevelopment.
Keywords: Urban redevelopment catalyst; Urban redevelopment; Urban catalyst; Washington Avenue; St. Louis; Street; Area Planning and Development (0341); Land Use Planning (0536); Urban Planning (0999)